2021
DOI: 10.3390/su13168813
|View full text |Cite
|
Sign up to set email alerts
|

What Do Freshmen Know about Sustainability? Analysing the Skill Gap among University Business Administration Students

Abstract: This study aims at creating and validating an instrument to assess the level of mastery in sustainability competencies of freshmen students in business-related studies. To reach this goal, a questionnaire that captures the level of acquisition of the competencies in sustainability is provided. A three-step process has been followed to analyse the results gathered among first-year students in two Spanish universities. First, eight confirmatory factor analyses were conducted to verify the grouping of the dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In terms of training received on sustainability, the difference between students in the first years of the degree course and those in higher courses is lower if they have received economic training before university entrance. When students are younger, they are more concerned about sustainability and its initiatives, so in high school the training received on sustainability in economics subjects is highly valued (Manresa et al , 2021). Later, when students think they already know a lot about the subject, they give less importance to it, because they have internalised it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of training received on sustainability, the difference between students in the first years of the degree course and those in higher courses is lower if they have received economic training before university entrance. When students are younger, they are more concerned about sustainability and its initiatives, so in high school the training received on sustainability in economics subjects is highly valued (Manresa et al , 2021). Later, when students think they already know a lot about the subject, they give less importance to it, because they have internalised it.…”
Section: Discussionmentioning
confidence: 99%
“…Social science students tend to have a more favourable attitude than pure science students (Talay et al , 2004). Manresa et al (2021) conclude that the introductory courses in economics that students receive in high school allow them to have an initial understanding and awareness of ethical implications. On the other hand, individuals who believe that their own efforts can solve environmental problems have more pro-sustainability attitudes and behaviours (Tobler et al , 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 1 more Smart Citation
“…Some papers present experiences in educational activities or program design [1][2][3], teaching-learning sequences [4], learning contexts that facilitate ESD [5][6][7][8] or a person-centered approach to professional soft skills development [9]. Others analyze the sustainability competence status at the study level [10][11][12] and faculty level [13,14], student perception and knowledge of sustainability learning [15][16][17][18][19], or likewise propose strategies at the university level for the integration of sustainability and the Sustainable Development Goals (SDGs) [20] in degree curricula [21][22][23].…”
mentioning
confidence: 99%
“…Manresa and colleagues [16], members of the aforementioned UMU-UIC working group, presented in an additional work an instrument to assess the domain level of sustainability competencies with which students begin university studies. In the specific case of business-related studies, the results revealed a highly heterogeneous freshmen level of development of sustainability competencies.…”
mentioning
confidence: 99%